Horizontal Local Governance and Social Inclusion: The Case of Municipality-Civil Society Engagement During Refugee Reception in Malmö, Sweden - Fry, Claudia; Islar, Mine (Frontiers in Political Science, 2021)
This study takes its departure from literature on the far-reaching engagements from civil society during the 2015 ‘refugee crisis’ in Europe as it seeks to understand the status of collaborative governance at the local level. It takes an in-depth look of Malmö, a city in Sweden which in 2015 became the centre for the Swedish refugee reception and solidarity initiatives. The study identifies challenges and opportunities of horizontal collaborations to develop the social dimension of city resilience. It includes eleven interviews with key actors from the civil society sector as well as from the municipality and utilizes theory on solidarities in the ‘refugee crisis’ together with social cohesion and inclusion as a framework for analysing data. This allows for a comprehensive appraisal of the (spatially produced) responses to migration from the city’s horizontal alliances. The findings suggest that there are diverse conclusions to be made about the long-term potential of horizontal collaborations in bringing about social resilience. On the one side it is discovered that short-term project collaborations may only serve to ‘fill the gap’ left by neo-liberal local governments and not bring about the structural change needed. On the other side, it is found that horizontal collaborations can be a strategy for civil society actors to influence more inclusive alternatives by bringing the realities of refugees into local policy making, particularly those refugees otherwise rendered invisible due to legal categorizations. Lastly, there are suggestions made for how to enhance the opportunities of horizontal collaborations in creating a socially cohesive, inclusive and resilient city.